ANALISIS PENGARUH KUALITAS AUDIT DAN REAL EARNING MANAGEMENT TERHADAP LABA OPERASIONAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2013-2016) - Dessy Kumaladewi (Program Studi Akuntansi - Universitas Islam Kuantan Singingi, 2019)
This study aims to test empiricall influence of audit quality and real earning management toward operational profit in the Manufacturing company registered in BEI period 2013-2016. The sampling technique used purposive sampling method which resulted in a sample of 40 sample. Researchers used multiple linear regression techniques analysis. The results showed that: 1). Audit quality does not have affect toward operational profit; 2). Real earning management has affect toward operational profit